Photo editing behaviour among Malaysian social media users: a conceptual framework - Jusoh, Noor Hafifah; Masrek, Mohamad Noorman; Ramli, Ishak; Mohd Rafee, Mohd Radzuan (Universiti Teknologi MARA, Perak, 2025)
Photo editing has become a widespread practice on social media, enabling users to manage their digital identities and present idealized versions of themselves online. While many studies have explored the psychological and social motivations behind photo editing, few have integrated these perspectives into a unified conceptual framework. This paper proposes a novel model that combines Self-Presentation Theory and the Theory of Planned Behaviour to explain how internal motivations, perceived social pressures (subjective norms), and behavioural intentions interact to shape photo editing practices. The framework posits that self-presentation influences users’ attitudes, subjective norms, and perceived behavioural control, which together form their intentions and ultimately lead to actual photo editing behaviour. This integrated approach provides a clearer understanding of digital self-modification, particularly within cultural contexts where appearance and social feedback are highly valued. The proposed model addresses a notable gap in existing research and offers a strong foundation for future empirical investigations and practical interventions aimed at fostering healthy digital self-awareness and mental well-being.